World Must Know about the Gigantic Contribution of Muslim Scientists in Laying Down of Foundations of Modern Sciences - Haque, Anwar Ul (International Journal of Pathology, 2021)
It is no exaggeration to say that modern sciences are standing on the solid platform established by the great Muslim scientists in the golden era of Muslim dominance (Dark ages in the West) (7th -14th centuries).1,2 Arabia which was baren till the end of 6th century became the center of excellence and accomplishments and the Arabs who were considered among the most backward in education and civilization suddenly became the pioneers and leaders in almost all fields of sciences and social sciences. Their inventions were peaceful and beneficial then and still profiting all human beings on this plant earth. With a loud and thunderous big bang Arabia and entire Muslim empire suddenly became the most fertile land for education and research which literally produced hundreds of great scientists in almost all fields of sciences and social sciences over 7-8 centuries.1,2